POTENTIAL OF ANAEROBIC DIGESTED DAIRY MANURE WASTEWATER ON ACCUMULATION OF ASTAXANTHIN, PROTEIN, AND PHYCOCYANIN IN MIXED CULTURE OF SPIRULINA PLATENSIS, CHLORELLA VULGARIS, AND HAEMATOCOCCUS PLUVIALIS - Nabila Reiza, Salma
The use of synthetic medium to fulfill the nutritional needs of microalgae growth requires relatively high costs. Anaerobic digested dairy manure wastewater (ADDMW) was suspected to have potential to substitute synthetic medium because it has a high nitrogen content and is abundantly available in cattle farms. Therefore, this study aims to reveal the potential of ADDMW waste in mixed cultures of S. platensis, C. vulgaris, and H. pluvialis on biomass growth and accumulation of astaxanthin, protein, and phycocyanin. This study began with optimation in 1 L glass bottles with variations of Zarrouk’s medium, 50% ADDMW (combination of Zarrouk:ADDMW 1:1 v/v), and 100% ADDMW. The specific growth rate and doubling time were analyzed based on dry weight. Astaxanthin levels were analyzed using High Performance Liquid Chromatography (HPLC) while protein and phycocyanin were analyzed spectrophotometrically. Scaling-up of mixed culture of S. platensis, C. vulgaris, and H. pluvialis was then carried out in open raceway pond (ORP) with the addition of 50% ADDMW treatment. The optimiation results showed that the best cultivation was obtained in Zarrouk medium (? = 0.20±0.01 /day, doubling time 3.48±0.13 days, astaxanthin 29.85±5.01 ?g/g, protein 47.25±7.82 mg/g, phycocyanin 12.74±0.80 mg/g). The specific growth rate, doubling time, and levels of astaxanthin, protein, and phycocyanin appeared to increase when cultivated in ORP, respectively to 0.18±0.01 /day, 3.96±0.13 days, 3.18±0.20 ?g/g, 35.31±1.04 mg/g, and 0.98±0.03 mg/g. It can be concluded that ADDMW waste has no potential to be used as an additional nutrient in mixed cultures S. platensis, C. vulgaris, and H. pluvialis. Microalgae cultivation in ORP has been shown to increase biomass growth and accumulation of astaxanthin, phycocyanin, and protein